Bioefficacy of Senna Occidentalis (L) Leaves Exract in the Management of Sitophilus Zeamais (Mots) (Maize Weevil) in Sudan Savannah Ecological Zone of Nigeria - B., Barau; A., Adams; M., Adelusi S.; S., Dan’azimi, M.; S., Jibia S.; J., Umar (Canadian Journal of Agriculture and Crops, 2020)
Ethanolic leaves extract of Senna occidentalis (L) at the rate of 1ml, 2ml and 3ml and a known weight of maize at 100g, 200g and 300g was used and tested for bioefficacy in the Laboratory for the management of Sitophilus zeamais Mots (maize weevil) on number of holes, oviposition response, antifeeding and germination percentage after maize storage for a diminutive period of six weeks in the Sudan Savannah Ecological Zone of Nigeria. A Complete randomized design (CRD) was used consisting of four treatments (including control) and repeated four times to determine the bioefficacy of Senna occidentalis L. in the management of the most destructive maize pest Sitophilus zeamais L. The result indicate that Senna occidentalis (L) leaves can serve as an antifeeding agent in managing the speed of infestation by S. zeamais in stored maize and positively affect the rate of oviposition of Sitophilus zeamais Mots. The result shows that Senna occidentalis L. has no effect on germination percentage observed during the maize seeds after the period of the storage. In conclusion, this research work suggested that the, management of Sitophilus zeamais (Mots) using Senna occidentalis (L) is promising and can be employed to store maize for a period of six weeks without disincentive to the quality of maize for consumption and for subsequent planting.